Christmas in Bethel [large type] - Evans, Richard Paul (Thorndike Press large print top shelf., 2024)
"Leigh Beth Stilton has never liked the holidays. Lingering impacts of an unstable home, abusive marriage, and the tragedies she sees as an EMT outweighs Leigh's care for Christmas cheer. Convinced she's not worth loving, Leigh decides she can't go on--until she reads the book Bethel by J.D. Harper. Harper's words speak directly to her and give her newfound strength. When Harper comes to town for a book signing, Leigh meets him, and the two immediately clock. Soon, she's swept up in the whirlwind of a new relationship. But when she discovers that J.D. hasn't been completely honest, her hopes are dashed. Can they reconcile and can Leigh learn to trust her heart?"--